Caractérisation morphologique et fonctionnelle des hémocytes chez l'huître plate, Ostrea edulis - Xue, Quiggang (Université de Bretagne Occidentale. Institut Européen de la Mer., 1998)
The mechanism that bivalve molluscs react to infectious agents are important research subjects in the fIeld of disease control studies for these animals. While the selection of disease resistant populations have made decisive progression in some species, the mechanism behinds these resistant phenomena is not yet clear so far. However, hemocytes must represent one of the key factors in the reaction process. Based on this hypothesis, the structure and function of European flat oyster, Ostrea edulis, hemocytes have been investigated in aid of different techniques in the present study. ln addition, Pacific oyster, Crassostrea gigas, hemocytes have been analysed in certain aspects so as to provide some results for comparison. European flat oyster and Pacific oyster hemocytes have been separated in three subpopulations corresponding respectively to granulocytes, large hyalinocytes and small agranulocytes by centrifugation in Percoll and Ficoll density gradient. These three separated hemocyte sub-populations as weil as the total hemocyte population demonstrate differences in electrophoretic patterns on SDS-PAGE. Differences in enzymatic activities have been revealed among total hemolymph, cell-free hemolymph, total hemocytes and separated hemocyte sub-populations and between Ostrea edulis and Crassostrea gigas. Bonamia ostreae infection induces enzymatic activity increase in the cell-free hemolymph fraction of its host. The hybridoma technique has been used for developing monoclonal antibodies specifically against Ostrea edulis hemocytes. One hybridoma clone (GP2,E11) which produces antibodies recognising all granulocytes was selected for application in granulocyte study. As a result, granulocyte tissue distribution and ontogenisis in developmental process of Ostrea edulis have been analysed by immunohistological technique in using antibody GP2E11. The antibody has also allowed to develop a procedure for analysing specifically labelled hemocytes with flow cytometry. Flow cytometric analyses of oyster hemocytes based on ...